2018
DOI: 10.1017/ice.2018.21
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hand Hygiene Ambassador and Implementation of Directly Observed Hand Hygiene Among Residents in Residential Care Homes for the Elderly in Hong Kong

Abstract: OBJECTIVEMultidrug-resistant organisms (MDROs) are increasingly reported in residential care homes for the elderly (RCHEs). We assessed whether implementation of directly observed hand hygiene (DOHH) by hand hygiene ambassadors can reduce environmental contamination with MDROs.METHODSFrom July to August 2017, a cluster-randomized controlled study was conducted at 10 RCHEs (5 intervention versus 5 nonintervention controls), where DOHH was performed at two-hourly intervals during daytime, before meals and medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…29 Hand hygiene is always the cornerstone to prevent transmission of COVID-19 but it is a one-off discontinuous process where hand contamination may occur easily between each alcoholic handrubbing or hand washing. Although we have successfully implemented directly observed hand hygiene (DOHH) by regular delivery of alcohol-based hand rub to conscious hospitalized patients and persons in residential care homes for the elderly before meal and medication rounds, [30][31][32] it may be difficult to practice DOHH in the community. Studies have also shown that wearing a mask with frequent hand hygiene significantly reduced transmission of seasonal influenza virus in the community setting.…”
Section: Discussionmentioning
confidence: 99%
“…29 Hand hygiene is always the cornerstone to prevent transmission of COVID-19 but it is a one-off discontinuous process where hand contamination may occur easily between each alcoholic handrubbing or hand washing. Although we have successfully implemented directly observed hand hygiene (DOHH) by regular delivery of alcohol-based hand rub to conscious hospitalized patients and persons in residential care homes for the elderly before meal and medication rounds, [30][31][32] it may be difficult to practice DOHH in the community. Studies have also shown that wearing a mask with frequent hand hygiene significantly reduced transmission of seasonal influenza virus in the community setting.…”
Section: Discussionmentioning
confidence: 99%
“…Unnecessary prescription of proton pump inhibitors and fluoroquinolones, which are risk factors for MRSA colonization as shown in our multivariate analysis, should be avoided. Practice of directly observed hand hygiene in resident before meal and medication rounds, 40 enforcement of environmental cleaning and disinfection, as well as implementation of universal MRSA decolonization should be incorporated into the bundle of control. 41,42 There are several limitations in this study.…”
Section: Discussionmentioning
confidence: 99%
“…McConeghy's 2017 study [76] was assessed at unclear risk for random sequence generation and allocation concealment, high risk for blinding of personnel and participants, outcome assessment and selective reporting; Temime's 2018 study [77] was at high risk for random sequence generation, unclear risk from allocation concealment, high risk from blinding of participants and personnel, performance assessment and incomplete data; and Yeung's 2011 study [78] was at unclear risk from random sequence generation, allocation concealment and selective reporting and high risk from blinding of participants and personnel and outcome assessment. There is only one c-RCT of hand hygiene for patients and staff which assessed bacterial contamination and there was a significant decrease in bacterial colonisation [79]. A 2020 systematic review of hand washing, distancing and mask wearing to prevent the transmission of SARS-CoV-2 identified 172 observational studies in 16 countries but no RCTs, and a meta-analysis of 44 non-randomised studies identified substantial protection by distancing more than one metre, hand washing, mask wearing and eye protection [80] (Table 9).…”
Section: Increasing the Use Of Medical Or Surgical Masks And Hand Hygiene To Reduce The Transmission Of Respiratory Virusesmentioning
confidence: 99%